Lactate Fluxes and Plasticity of Adipose Tissues: A Redox Perspective - Lagarde, Damien; Jeanson, Yannick; Portais, Jean-Charles; Galinier, Anne; Ader, Isabelle; Casteilla, Louis; Carrière, Audrey (Frontiers in Physiology, 2021)
Lactate, a metabolite produced when the glycolytic flux exceeds mitochondrial oxidative capacities, is now viewed as a critical regulator of metabolism by acting as both a carbon and electron carrier and a signaling molecule between cells and tissues. In recent years, mounting evidence reports its key role in white, beige and brown adipose tissues biology, and highlights new mechanisms by which lactate participates to the maintenance of whole body energy homeostasis. Lactate displays a wide range of biological effects in adipose cells through its binding to the membrane receptor but also through its transport and subsequent effect on intracellular metabolism notably on redox balance. This review explores how lactate regulates adipocyte metabolism and plasticity by balancing intra-cellular redox state and by regulating specific signaling pathways. We also emphasize the contribution of adipose tissues to the regulation of systemic lactate metabolism, their roles in redox homeostasis and related putative physio-pathological repercussions associated with their decline in metabolic diseases and aging.